Enhancing Teacher Competency Through Psychoeducation: A Study on Knowledge Improvement Regarding Children with Special Needs at Islamic Greens School Bekasi - Wahjusaputri, Sintha; Agustiningsih, Agustiningsih; Fitrianingsih, Diah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to examine psychoeducation's influence on enhancing teacher proficiency in comprehending and assisting students with special needs at Islamic Greens School, located in Tangerang City. The research employed a quasi-experimental method, utilizing pre-test and post-test measures to evaluate the level of teacher knowledge before and following the intervention. This study was conducted at The Inclusive Islamic Green School Bekasi, which caters to students from elementary, junior high, and high school levels. A total of 31 teachers participated in the survey. The results demonstrated a substantial improvement in teacher comprehension of the distinct difficulties and educational requirements of children with special needs, as indicated by an average pre-test score of 65.48 and an average post-test score of 87.42. The psychoeducational program successfully enhanced teacher proficiency equipped them with the necessary resources to cultivate an inclusive learning environment and offered continuous professional development to address students' requirements. Implementing psychoeducational efforts in schools can have significant repercussions, resulting in adopting more inclusive practices. This, in turn, benefits both instructors and students by creating a more inclusive educational environment.Â